A control method for perovskite quantum dot display array based on TFT drive array

By regulating the impedance parameters of the TFT-driven array and perovskite quantum dot LED, the problem of mismatch between the impedance of the perovskite quantum dot LED and the TFT-driven array in the prior art is solved, and the normal operation and high brightness of the TFT-driven perovskite LED display array is achieved.

CN115050917BActive Publication Date: 2025-02-28杭州领挚科技有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210812457.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-11
Publication Date
2025-02-28
Estimated Expiration
2042-07-11

AI Technical Summary

Technical Problem

The prior art is difficult to match the working impedance of perovskite quantum dot LEDs and the output impedance of the TFT-driven array, making it difficult for the TFT-driven perovskite LED display array to work normally.

Method used

By regulating the equivalent resistance of the TFT-driven array and the equivalent resistance of the perovskite quantum dot LED devices, specific methods include selecting different semiconductor layers and designing different width-length ratios, and matching the impedance of both by adjusting the carbon chain length and ligand density of the perovskite quantum dot surface ligand.

Benefits of technology

The working impedance of the perovskite quantum dot LED device matches the output impedance of the TFT-driven array, ensuring the normal operation and high brightness of the TFT-driven perovskite LED display array.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present application provides a perovskite quantum dot active light-emitting display array based on a TFT drive array, wherein the source or drain of the TFT drive array is connected to the positive electrode of an indium tin oxide (ITO) thin film; the ITO is used as one of the electrodes of a perovskite quantum dot light-emitting diode; the perovskite quantum dot light-emitting diode comprises a hole injection layer, a hole transport layer, a perovskite quantum dot light-emitting layer, an electron transport layer, and an electrode layer. The present application uses a TFT drive array as a substrate for a perovskite quantum dot LED, and by adjusting the carbon chain length and ligand density of the ligands on the surface of the perovskite quantum dot, the equivalent resistance of the perovskite quantum dot LED is matched with the output equivalent resistance of the TFT drive array, thereby directly preparing a perovskite quantum dot three-primary color active light-emitting array on the TFT drive array.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of light-emitting display, and in particular to a perovskite quantum dot active light-emitting array and a preparation method thereof. Background Art

[0002] The existing technologies in the optoelectronic display industry are TFT-LCD and TFT-OLED (AMOLED). Both technologies use thin-film field-effect transistor (TFT) arrays to control display pixels. The TFT drive array not only improves the response speed of the display screen, but also can accurately control the display grayscale. The display panel using TFT as the drive circuit has more realistic colors. In recent years, metal halide perovskite materials have attracted widespread attention in the display field for their superior luminescence performance. Perovskite quantum dots have continuously adjustable luminescence wavelength, narrow half-peak width of luminescence spectrum, and high color purity. Their optoelectronic properties are closely related to the perovskite composition, the selection of organic ligands, the morphology and size of nanostructures, which provides the possibility of realizing perovskite optoelectronic devices for various purposes. In the past few years, the efficiency of perovskite quantum dot LED devices has developed rapidly, and the external quantum efficiency (EQE) has rapidly increased from less than 1% to more than 20%. Therefore, perovskite quantum dots have the potential to realize TFT-driven active light-emitting LED display arrays through solution processing.

[0003] To integrate perovskite quantum dot LEDs with TFT drive arrays, a key technical issue that has been overlooked is the matching of the operating impedance of the LED and the output impedance parameters of the TFT. When the TFT is in the on state, the connected perovskite quantum dot LED device acts as a load, which can be equivalent to a TFT equivalent resistor and an LED device equivalent resistor in series. Only when the equivalent resistance of the perovskite quantum dots is in the same order of magnitude as the on-state resistance of the TFT, can sufficient TFT output voltage be divided to light up the perovskite quantum dot LED device. However, since the impedance of the perovskite quantum dot LED is affected by factors such as the material, thickness, and interface of each functional layer of the LED device, there are challenges in matching the TFT output impedance, making it difficult to achieve a TFT drive array perovskite LED display array.

[0004] Therefore, it is urgent to develop a method to effectively regulate the impedance of perovskite quantum dot LEDs under working conditions to match the output impedance of the TFT driver array used, thereby solving one of the key technical difficulties in the normal operation of TFT-driven perovskite LED display arrays. Summary of the invention

[0005] The present invention provides a perovskite quantum dot active light-emitting display array based on a TFT drive array, using the TFT drive array as a substrate of a perovskite quantum dot LED, and directly preparing a perovskite quantum dot LED device on the TFT drive array. The equivalent resistance of the TFT drive array can be regulated by means of selecting different semiconductor layers, setting the thickness of the semiconductor layer, designing different width-to-length ratios, and the like. The equivalent resistance of the perovskite quantum dot LED device mainly depends on the conductivity of the quantum dot light-emitting layer material. Specifically, it can be regulated by adjusting the carbon chain length and ligand density of the ligand on the surface of the perovskite quantum dot to match the equivalent resistance of the TFT drive array, and preparing a perovskite quantum dot three-primary color active light-emitting array.

[0006] The present invention provides a perovskite quantum dot active light-emitting display array based on a TFT driving array, which comprises, from bottom to top, a TFT driving array, a hole injection layer, a hole transport layer, a perovskite quantum dot light-emitting layer, an electron transport layer, a cathode and a glass encapsulation layer.

[0007] A method for preparing a perovskite quantum dot active light-emitting display array based on a TFT drive array comprises the following steps:

[0008] Step 1: TFT driver array cleaning

[0009] Preparation and surface treatment of TFT drive array: Through the traditional photolithography process, the gate layer, insulating layer, semiconductor layer, source and drain layer, passivation layer and top electrode layer are prepared in sequence to obtain the TFT drive array. The TFT drive array substrate is placed in a beaker, poured into acetone for ultrasonic cleaning for 15 minutes, rinsed with deionized water three times, poured into deionized water for ultrasonic cleaning for 15 minutes, poured out the water and poured into anhydrous ethanol for ultrasonic cleaning for 15 minutes. After drying the TFT drive array substrate with nitrogen, it is placed in a plasma generator and treated with oxygen plasma to further clean the substrate surface.

[0010] Step 2: Preparation of hole injection layer

[0011] The TFT driving array substrate was fixed on the spin coater by adsorption through a vacuum pump, and the PEDOT:PSSAI4083 aqueous solution was sucked with a syringe, and 30 μl was dropped on the center of the substrate. The substrate was spun at a high speed of 4000 rpm. After the spin coating was completed, the substrate was placed on a hot stage and annealed at 150°C for 15 minutes.

[0012] Step 3: Preparation of hole transport layer

[0013] The TFT drive array substrate was fixed on the spin coater by vacuum pump adsorption, and the hole transport layer material poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) chlorobenzene solution (5-20 mg / mL) was sucked with a pipette, and 30 μL was dropped on the center of the substrate. High-speed spin coating was performed at 2000 rpm. After the spin coating was completed, the substrate was placed on a hot stage for annealing at 120°C for 15 minutes. The hole transport layer material includes, but is not limited to, one or more of poly(9-vinylcarbazole) (PVK), poly[(4,4′-(N-(4-sec-butylphenyl)diphenylamine)] (PolyTPD), poly[9,9-dioctylfluorene-co-N-[4-(3-methylpropyl)]-diphenylamine] (TFB), and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA). Through the concentration of the hole transport layer material and the spin coating speed, the thickness of the hole transport layer can be adjusted within the range of 10-100 nm, thereby adjusting the working impedance of the perovskite quantum dot LED.

[0014] Step 4: Preparation of quantum dot light-emitting layer

[0015] The perovskite quantum dots include red, green and blue perovskite quantum dots, which are prepared by solution process. The specific preparation method is as follows:

[0016] Synthesis of perovskite quantum dots: Take one of lead bromide, lead acetate, lead carbonate and tetra-n-octylammonium bromide and stir and dissolve them in toluene to obtain a lead source solution; take one of cesium carbonate and cesium acetate and dissolve them in octanoic acid to obtain a cesium source solution; dissolve one or more of the ligands didodecyldimethylammonium bromide, dodecylbenzenesulfonic acid, n-octanoic acid, oleic acid, di(2,4,4-trimethylpentyl)phosphonic acid in toluene to obtain a ligand solution. At room temperature, add a certain amount of cesium source solution to the lead source solution, stir and react for 2 minutes, the color of the solution changes from colorless to yellow, and green light perovskite quantum dots are generated. Continue to add ligand solution to the reaction solution, the solution becomes bright yellow, and the surface defects of the quantum dots are passivated. By changing the type of ligand solution and the concentration and volume of the ligand solution, the carbon chain length and ligand density of the ligands on the surface of the quantum dots can be regulated, thereby changing the impedance of the quantum dot film.

[0017] Purification of perovskite quantum dots: centrifuge the original solution after the reaction at high speed, discard the precipitate, take the supernatant, add the anti-solvent ethyl acetate at twice the volume of the supernatant, centrifuge the solution at high speed immediately after precipitation, discard the supernatant after centrifugation, and redissolve the precipitate in octane. Increasing the number of purifications can reduce the ligand density on the surface of perovskite quantum dots, thereby adjusting the impedance of the quantum dot film. The higher the ligand density, the greater the impedance of the perovskite quantum dot film. When purified once, the ligand density is high, about 1-5 / nm2, and the impedance of the perovskite quantum dot film is large; when purified twice, the ligand density is about 0.1-1 / nm2.

[0018] Preferably, the surface ligands of the perovskite quantum dots include, but are not limited to, any one group or a combination of oleylamine, oleic acid, dodecylbenzoic acid, didodecyldimethylammonium bromide, bis(decyldimethylammonium bromide), didodecyldimethylammonium chloride, and bis(2,4,4-trimethylpentyl)phosphonic acid.

[0019] Perovskite quantum dot film formation: Take the synthesized perovskite quantum dot solution and drop it in the center of the substrate coated with the hole injection layer and the hole transport layer, and control the thickness of the quantum dot light-emitting layer to 10-100nm by controlling the spin coating speed.

[0020] Step 5: Preparation of electron transport layer

[0021] Place the TFT drive array substrate coated with the hole injection layer, hole transport layer and perovskite quantum dot light-emitting layer face down into the metal mask and then into the coating machine. Evacuate to 5*10-4Pa, turn on the organic heating power supply, vaporize the electron transport layer material and form a film on the LED device. The evaporation rate should not exceed The electron transport layer material includes one or more of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 2,4,6-tris[3-(diphenylphosphino)phenyl]-1,3,5-triazole (PO-T2T), di[2-((oxy)diphenylphosphino)phenyl]ether (DPEPO), and 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]bipyridine (TmPyPB). The thickness of the electron transport layer is 10nm-100nm.

[0022] Step 6: Preparation of metal electrodes

[0023] After the electron transport layer is evaporated, wait for 5-10 minutes, turn on the metal heating power supply, and evaporate LiF and Al. The LiF evaporation rate is Al evaporation rate does not exceed The negative electrode material includes one or more of Al, LiF\Al, Ag, LiF\Ag. The thickness of LiF is 1-5nm, and the thickness of Al is 50nm-1μm.

[0024] Step 7: Preparation of glass encapsulation layer

[0025] Apply UV curing glue to the edges of the encapsulation sheet and encapsulate the device after curing under UV light.

[0026] Compared with the prior art, the beneficial effect of the present application is that by adjusting the impedance of each functional layer of the perovskite quantum dot LED, the impedance of the LED under working conditions can match the output impedance of the TFT drive array, thereby achieving the normal operation of the TFT driven perovskite LED display array. The thickness adjustment of the hole transport layer, quantum dot light emitting layer and electron transport layer can make the working impedance of the LED within 10 2 -10 4 The ligand density and carbon chain length of the quantum dot light-emitting layer further adjust the working impedance of the LED to 10 4 -10 8 Ohms. Therefore, the working impedance of the LED device can be 10 2 -10 8 The output impedance of commercial TFT drive arrays is generally 10 3 -10 5 Ohm range. The technical method of this project can match the working impedance of LED devices to various TFT drive arrays, and realize the lighting of LED display arrays. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a schematic diagram of the TFT driving array;

[0028] Figure 2 is a structural schematic diagram of the perovskite quantum dot active light-emitting array based on the TFT driving array;

[0029] Figure 3 is the LED working impedance regulated by the thickness of the LED functional layer and the quantum dot ligands;

[0030] Figure 4 is a physical photo of the perovskite quantum dot active light-emitting array based on the TFT driving array;

[0031] Figure 5 It is the photoluminescence spectrum of the perovskite quantum dot active light-emitting array based on the TFT driving array. DETAILED DESCRIPTION

[0032] Below, the present application is further described in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.

[0033] Example 1

[0034] The TFT drive array substrate was ultrasonically cleaned with acetone-water-anhydrous ethanol for 15 minutes respectively, and then the substrate surface was treated with plasma. PEDOT:PSS aqueous solution was spin-coated at 4000 rpm for 50 seconds and annealed at 150°C for 15 minutes. PTAA chlorobenzene solution was spin-coated at 2000 rpm for 50 seconds and annealed at 120°C for 20 minutes. Red light perovskite quantum dots were spin-coated at 2000 rpm for 50 seconds. The red light perovskite quantum dots were synthesized by hot injection. The oleylamine oleic acid ligand with a carbon chain length of 18 carbons was replaced with a bis(2,4,4-trimethylpentyl)phosphonic acid ligand through ligand exchange, and then purified and cleaned twice. The electron transport layer TPBi was prepared by vacuum thermal evaporation at a rate of The thickness is 40nm. The negative electrode LiF and AI are prepared by vacuum thermal evaporation, and the LiF evaporation rate is The thickness is 1nm and the Al evaporation rate is The thickness is 100nm.

[0035] The red light perovskite quantum dots prepared by this method have a moderate carbon chain length and a low ligand density, and can match the equivalent resistance of a TFT drive array. The active light-emitting array prepared with the red light perovskite quantum dots can be lit up with high brightness.

[0036] Example 2

[0037] The TFT drive array substrate was ultrasonically cleaned with acetone-water-anhydrous ethanol for 15 minutes respectively, and then the substrate surface was treated with plasma. PEDOT:PSS aqueous solution was spin-coated at 4000 rpm for 50 seconds and annealed at 150°C for 15 minutes. PTAA chlorobenzene solution was spin-coated at 2000 rpm for 50 seconds and annealed at 120°C for 20 minutes. Green light perovskite quantum dots were spin-coated at 2000 rpm for 50 seconds. The green light perovskite quantum dots were synthesized by room temperature method. The in-situ ligands were dodecylbenzenesulfonic acid and didodecyldimethylammonium bromide. The carbon chain length was 12 carbons and they were purified and cleaned twice. The electron transport layer TPBi was prepared by vacuum thermal evaporation at a rate of The thickness is 40nm. The negative electrode LiF and AI are prepared by vacuum thermal evaporation, and the LiF evaporation rate is The thickness is 1nm and the Al evaporation rate is The thickness is 100nm.

[0038] The green light perovskite quantum dots prepared by this method have a moderate carbon chain length and a low ligand density, and can match the equivalent resistance of a TFT drive array. The active light-emitting array prepared with the green light perovskite quantum dots can be lit up with high brightness.

[0039] Example 3

[0040] The TFT drive array substrate was ultrasonically cleaned with acetone-water-anhydrous ethanol for 15 minutes respectively, and then the substrate surface was treated with plasma. PEDOT:PSS aqueous solution was spin-coated at 4000 rpm for 50 seconds and annealed at 150°C for 15 minutes. PTAA chlorobenzene solution was spin-coated at 2000 rpm for 50 seconds and annealed at 120°C for 20 minutes. Blue light perovskite quantum dots were spin-coated at 2000 rpm for 50 seconds. The blue light perovskite quantum dots were synthesized by room temperature method. The in-situ ligand was didodecyldimethylammonium chloride with a carbon chain length of 12 carbons and purified and cleaned twice. The electron transport layer TPBi was prepared by vacuum thermal evaporation at a rate of The thickness is 40nm. The negative electrode LiF and AI are prepared by vacuum thermal evaporation, and the LiF evaporation rate is The thickness is 1nm and the Al evaporation rate is The thickness is 100nm.

[0041] The blue light perovskite quantum dots prepared by this method have a moderate carbon chain length and a low ligand density, and can match the equivalent resistance of a TFT drive array. The active light-emitting array prepared with the blue light perovskite quantum dots can be lit up with high brightness.

[0042] Comparative Example 1

[0043] The TFT drive array substrate was ultrasonically cleaned with acetone-water-anhydrous ethanol for 15 minutes respectively, and then the substrate surface was treated with plasma. PEDOT:PSS aqueous solution was spin-coated at 4000 rpm for 50 seconds and annealed at 150°C for 15 minutes. PTAA chlorobenzene solution was spin-coated at 2000 rpm for 50 seconds and annealed at 120°C for 20 minutes. Red light perovskite quantum dots were spin-coated at 2000 rpm for 50 seconds. The red light perovskite quantum dots were synthesized by hot injection, purified and cleaned twice, without ligand exchange process, and the ligands on the surface of the quantum dots were oleylamine and oleic acid, and the carbon chain length was 18 carbons. The electron transport layer TPBi was prepared by vacuum thermal evaporation at a rate of The thickness is 40nm. The negative electrode LiF and AI are prepared by vacuum thermal evaporation, and the LiF evaporation rate is The thickness is 1nm and the Al evaporation rate is The thickness is 100nm.

[0044] The red light perovskite quantum dot active light-emitting array prepared by this method cannot well match the equivalent impedance of the TFT drive array in the on state due to the long carbon chain of the quantum dot surface ligands, large equivalent resistance and poor conductivity, and the device cannot be turned on.

[0045] Comparative Example 2

[0046] The TFT drive array substrate was ultrasonically cleaned with acetone-water-anhydrous ethanol for 15 minutes respectively, and then the substrate surface was treated with plasma. The PEDOT:PSS aqueous solution was spin-coated at 4000 rpm for 50 seconds and annealed at 150°C for 15 minutes. The PTAA chlorobenzene solution was spin-coated at 2000 rpm for 50 seconds and annealed at 120°C for 20 minutes. The green light perovskite quantum dots were spin-coated at 2000 rpm for 50 seconds. The green light perovskite quantum dots were synthesized by room temperature method. The in-situ ligands were dodecylbenzenesulfonic acid and didodecyldimethylammonium bromide. The carbon chain length was 12 carbons and only purified and cleaned once. The electron transport layer TPBi was prepared by vacuum thermal evaporation at a rate of The thickness is 40nm. The negative electrode LiF and AI are prepared by vacuum thermal evaporation, and the LiF evaporation rate is The thickness is 1nm and the Al evaporation rate is The thickness is 100nm.

[0047] The green light perovskite quantum dot active light-emitting array prepared by this method cannot match the equivalent impedance of the TFT drive array in the on state well because the green light perovskite quantum dots have high surface ligand density, large equivalent resistance and poor conductivity. The device has a high turn-on voltage, extremely low brightness and low external quantum efficiency.

[0048] The above describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and the specification only describe the principles of the present application. The present application may have various changes and improvements without departing from the spirit and scope of the present application, and these changes and improvements fall within the scope of the present application for which protection is sought. The scope of protection claimed by the present application is defined by the attached claims and their equivalents.

Claims

1. A method for controlling a perovskite quantum dot display array based on a TFT drive array, characterized in that: include: First, perovskite quantum dots are synthesized by a ligand solution method, and then a perovskite quantum dot LED is grown by a solution process on a TFT drive array, wherein the equivalent resistance of the perovskite quantum dot LED is controlled within 10 by adjusting the ligand carbon chain length and ligand density on the surface of the perovskite quantum dots. 2 -10 7 The ohm range is adjustable, so that the equivalent resistance of the perovskite quantum dot LED matches the TFT output impedance. The specific regulation process is as follows: The carbon chain length of the ligand used in the ligand solution method is regulated to be 6-18 carbons. The longer the carbon chain length, the greater the equivalent resistance of the perovskite quantum dot LED. The number of operations for washing the ligand purification product in the ligand solution method is regulated to be 2-4 times. The fewer the number of operations, the greater the ligand density and the greater the equivalent resistance of the perovskite quantum dot LED.

2. The method according to claim 1, characterized in that The ligand solution method for synthesizing perovskite quantum dots comprises the following steps: S1. Obtaining a lead source solution: Take one of lead bromide, lead acetate, lead carbonate and tetra-n-octylammonium bromide and stir and dissolve in toluene; S2. Obtaining a cesium source solution: dissolving one of cesium carbonate and cesium acetate in octanoic acid; S3. Obtaining a ligand solution: dissolving one or more of the ligands didodecyldimethylammonium bromide, dodecylbenzenesulfonic acid, n-octanoic acid, oleic acid, and bis(2,4,4-trimethylpentyl)phosphonic acid in toluene; S4. Reaction to generate perovskite quantum dots: At room temperature, add the cesium source solution to the lead source solution, stir and react for 2 minutes, the color of the solution changes from colorless to yellow, and perovskite quantum dots are generated. Continue to add the ligand solution to the reaction solution, and the solution becomes bright yellow; S5. Clean the ligand to purify the product: centrifuge the original solution after the reaction at high speed, discard the precipitate, take the supernatant, add the anti-solvent ethyl acetate in an amount twice the volume of the supernatant, centrifuge the solution at high speed immediately after precipitation occurs, discard the supernatant after centrifugation, dissolve the precipitate again and disperse it in octane, and repeat this step for a preset number of times.

3. The method according to claim 1, characterized in that The perovskite quantum dots are red perovskite quantum dots, green perovskite quantum dots or blue perovskite quantum dots, and the molecular formula of the perovskite quantum dots is: APbX3, wherein A is selected from alkylamine salt cations, alkyl amidine salt cations and cesium ions, and X is a halogen element.

4. The method according to claim 1, characterized in that: The size of perovskite quantum dots is 3-20nm, and the thickness of the light-emitting layer formed is 3-100nm.

5. The method according to claim 1, characterized in that The source or drain of the TFT driving array is connected to the positive electrode of indium tin oxide (ITO); the ITO is used as one of the electrodes of the perovskite quantum dot light-emitting diode; the perovskite quantum dot light-emitting diode includes a hole injection layer, a hole transport layer, a perovskite quantum dot light-emitting layer, an electron transport layer, and an electrode layer.

6. The method according to claim 1, characterized in that The TFT drive array can light up the LED under the voltage of ±14V, the brightness range is adjustable from 1 to 100000 nits, and the output impedance is 10 2 -10 6 ohm.

7. The method according to claim 5, characterized in that The hole transport layer includes: one or more of poly(9-vinylcarbazole) (PVK), poly[(4,4′-(N-(4-sec-butylphenyl)diphenylamine)] (PolyTPD), poly[9,9-dioctylfluorene-co-N-[4-(3-methylpropyl)]-diphenylamine] (TFB), and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA).

8. The method according to claim 7, characterized in that The hole transport layer thickness is 10-100nm and the impedance is 10 2 -10 5 ohm.

9. The method according to claim 5, characterized in that The electron transport layer includes one or more of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), 2,4,6-tris[3-(diphenylphosphino)phenyl]-1,3,5-triazole (PO-T2T), di[2-((oxy)diphenylphosphino)phenyl]ether (DPEPO), and 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1"-terphenyl]-3,3"-diyl]bipyridine (TmPyPB).

10. The method according to claim 9, characterized in that The thickness of the electron transport layer is 10-100nm, and the impedance is 10 2 -10 5 ohm.

Citation Information

Patent Citations

  • Quantum dot light-emitting diode

    CN111384254A

  • Preparation method of quantum dot light-emitting diode

    CN114695716A